2016
DOI: 10.1002/2327-6924.12312
|View full text |Cite
|
Sign up to set email alerts
|

HPV and HPV vaccine information among a national sample of college and university websites

Abstract: Background and purpose To describe the availability of human papillomavirus (HPV) and HPV vaccine information accessible to college students via official college and university websites. Methods A review and analysis of HPV and HPV vaccination information abstracted from a national sample (n = 214) of college/university websites. Three abstractors systematically evaluated quality and quantity of vaccination, sexual health, and HPV disease information from health service webpages. Conclusions The majority of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 16 publications
0
3
1
Order By: Relevance
“…The disparity between men and women may be closing as a result of an increase in overall awareness, with no significant differences by sex found in the present study. This is an apparent improvement compared with earlier research that found that college women were significantly more aware of HPV than college men were (Fontenot, Fantasia, Sutherland, et al, 2016; Gerend & Magloire, 2007; Osazuwa-Peters et al, 2017; Sandfort & Pleasant, 2009). Although awareness of the virus itself may be improving among men, we can continue this trend by ensuring that men are the recipients of detailed education efforts.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…The disparity between men and women may be closing as a result of an increase in overall awareness, with no significant differences by sex found in the present study. This is an apparent improvement compared with earlier research that found that college women were significantly more aware of HPV than college men were (Fontenot, Fantasia, Sutherland, et al, 2016; Gerend & Magloire, 2007; Osazuwa-Peters et al, 2017; Sandfort & Pleasant, 2009). Although awareness of the virus itself may be improving among men, we can continue this trend by ensuring that men are the recipients of detailed education efforts.…”
Section: Discussioncontrasting
confidence: 59%
“…Vaccine acceptability is correlated with awareness and knowledge of HPV (Ferris et al, 2009; Gerend & Barley, 2009; Hunter & Weinstein, 2016; Lenselink et al, 2008); yet, until recently, little research has included college-aged men’s attitudes toward HPV vaccination (Brewer, Ng, McRee, & Reiter, 2010; Fitzgerald, Savage, & Hegarty, 2014). Research focused on characterizing disparities in awareness and knowledge is especially needed in diverse areas, such as the state of Florida, which has some of the lowest HPV vaccination rates in the country as well as some of the highest cervical cancer rates (Fontenot, Fantasia, Sutherland, & Lee-St. John, 2016). An evaluation of what men and women in college know, think, and do about the threat of HPV can offer possible solutions to remedy the underutilization of the HPV vaccine in a population at high risk for contracting this preventable infection.…”
mentioning
confidence: 99%
“…40 Several studies find women surpassing men in HPV-related knowledge. 41,42 Vaccine initiation ( ‡1 dose) in Hispanic students was 41%, similar to non-Hispanics in this sample, despite reporting receiving less HPV-related information before involvement in the intervention. Hispanic adolescents surveyed in a 2015 Florida study reported 61.7% of women and 50.1% of men having received at least one dose of HPV vaccine, 43 a higher coverage than observed in our study.…”
Section: Discussionmentioning
confidence: 52%
“…Student health centers could be an ideal setting for vaccine naïve young adults to obtain preventive vaccinations; specifically, many students utilize these resources for primary care ( Turner and Keller, 2015 ), and over 12 million young adults under age 25 are enrolled in American colleges and universities ( NCES, 2018 ); however; campus health centers may not be providing easily accessible information about HPV vaccine education or availability. A recent analysis of college health center websites at 214 American universities found that only 50% mentioned HPV vaccine and only 32% of those provided any additional information such as costs and availability ( Fontenot et al, 2016 ). Research regarding health communication approaches to increase HPV vaccine suggests a preference for strong, straight-forward recommendations ( Malo et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%